Criteria for validation and selection of cognitive tests for investigating the effects of foods and nutrients. (22nd February 2014) - de, Celeste A; Dye, Louise; de, Eveline A; Butler, Laurie; Fletcher, John; Lamport, Daniel J; Latulippe, Marie E; Spencer, Jeremy PE; Wesnes, Keith
<x xml:space="preserve">Abstract</x> This review is an output of the International Life Sciences Institute (ILSI) Europe Marker Initiative, which aims to identify evidence‐based criteria for selecting adequate measures of nutrient effects on health through comprehensive literature review. Experts in cognitive and nutrition sciences examined the applicability of these proposed criteria to the field of cognition with respect to the various cognitive domains usually assessed to reflect brain or neurological function. This review covers cognitive domains important in the assessment of neuronal integrity and function, commonly used tests and their state of validation, and the application of the measures to studies of nutrition and nutritional intervention trials. The aim is to identify domain‐specific cognitive tests that are sensitive to nutrient interventions and from which guidance can be provided to aid the application of selection criteria for choosing the most suitable tests for proposed nutritional intervention studies using cognitive outcomes. The material in this review serves as a background and guidance document for nutritionists, neuropsychologists, psychiatrists, and neurologists interested in assessing mental health in terms of cognitive test performance and for scientists intending to test the effects of food or food components on cognitive function.